Lithosphere architecture characterized by crust–mantle decoupling controls the formation of orogenic gold deposits. Issue 3 (16th November 2022) - Hou, Zengqian; Wang, Qingfei; Zhang, Haijiang; Xu, Bo; Yu, Nian; Wang, Rui; Groves, David I; Zheng, Yuanchuan; Han, Shoucheng; Gao, Lei; Yang, Lin
ABSTRACT: This study, via combined analysis of geophysical and geochemical data, reveals a lithospheric architecture characterized by crust–mantle decoupling and vertical heat-flow conduits that control orogenic gold mineralization in the Ailaoshan gold belt on the southeastern margin of Tibet. The mantle seismic tomography indicates that the crust–mantle decoupled deformation, defined from previous seismic anisotropy analysis, was formed by upwelling and lateral flow of the asthenosphere, driven by deep subduction of the Indian continent. Our magnetotelluric and seismic images show both a vertical conductor across the Moho and high Vp/Vs anomalies both in the uppermost mantle and lowest crust, suggesting that crust–mantle decoupling promotes ponding of mantle-derived basic melts at the base of the crust via a heat-flow conduit. Noble gas isotope and halogen ratios of gold-related ore minerals indicate a mantle source of ore fluid. A rapid decrease in Cl/F ratios of lamprophyres under conditions of 1.2 GPa and 1050°C suggests that the ore fluid was derived from degassing of the basic melts. Similar lithospheric architecture is recognized in other orogenic gold provinces, implying analogous formational controls. Abstract : Multidisciplinary research reveals steps of orogenic gold deposits, including mantle partial melting, basic magma ponding and ore fluid release at the base of the crust with decoupled formation from mantle, as well as fluid migration in the middle-upper crust.